Nutrition is associated with differences in multisensory integration in healthy older adults - Kenny, Rose; Newell, Fiona (My University, 2024)
Diet can influence cognitive functioning in older adults and is a modifiable risk factor for cognitive decline. However, it is unknown if an association exists between diet and lower-level processes in the brain underpinning cognition, such as multisensory integration. We investigated whether temporal multisensory integration is associated with daily intake of fruit and vegetables (FV) or products high in fat/sugar/salt (FSS) in a large sample (N = 2,693) of older adults (mean age = 64.06 years, SD = 7.60; 56% female) from The Irish Longitudinal Study on Ageing (TILDA). Older adults completed a Food Frequency Questionnaire from which the total number of daily servings of FV and FSS items respectively was calculated. Older adults’ susceptibility to the Sound Induced Flash Illusion (SIFI) measured the temporal precision of audio-visual integration, which included three audio-visual Stimulus Onset Asynchronies (SOAs): 70, 150 and 230 ms. Older adults who self-reported a higher daily consumption of FV were less susceptible to the SIFI at the longest versus shortest SOAs (i.e. increased temporal precision) compared to those reporting the lowest daily consumption (p = .013). In contrast, older adults reporting a higher daily consumption of FSS items were more susceptible to the SIFI at the longer versus shortest SOAs (i.e. reduced temporal precision) compared to those reporting the lowest daily consumption (p < .001). The temporal precision of multisensory integration is differentially associated with levels of daily consumption of FV versus products high in FSS, consistent with broader evidence that habitual diet is associated with brain health.
PUBLISHED
Keywords: Ageing, audition, diet, multisensory, nutrition, perception, sound induced flash illusion, vision; Ageing